Content-based image indexing and retrieval - Lim, Chin Yong. (2012)
This report provides an empirical study on content-based image indexing and retrieval. The report begins with a description of its purpose and research focus. Next it presents the theoretical background for the techniques commonly used in machine learning. The main discussion deals with the experimental setup to evaluate the performance of content-based using SPK-BOW model. The final chapter provides concluding remarks and considerations for future research and development.